(untitled) (Indian Journal of Animal Production and Management, 2015)
Eighteen crossbred lactating cows were randomly selected for the experiment on the basis of live weight and milk yield. The animals were divided into three groups and allotted to three dietary treatments, viz.- T0, T1 and T2. Animals in T0 groups were fed by conventional method (concentrate and roughages fed separately) and feeding of animals in T1 and T2 were done in the form of total mixed ration, where the roughage: concentrate ratio was maintained at 40:60 and 50:50, respectively. The feeding trial was conducted for 120 days. Milk and blood samples were analyzed at fortnightly and monthly interval respectively. The percent total solids, protein, fat, SNF and lactose content in milk was comparable among the treatments. Thus, feeding system does not have any significant impact on the constituents of milk and blood.